PELAKSANAAN PENILAIAN HASIL BELAJAR ANAK USIA DINI DI TK LKIA II PONTIANAK - Umi Safitri; Aunurrahman Aunurrahman; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research is "How is the implementation of the assessment of early childhood learning outcomes by teachers in Pontianak LKIA II Kindergarten?". This study aims to determine the implementation of the assessment of early childhood learning outcomes by teachers in Pontianak LKIA II Kindergarten. The method used in this research is descriptive qualitative method. Data collection techniques are interview, observation and documentation techniques. The subjects of the research were the class teacher and the head of the LKIA II Kindergarten Pontianak. The research data were tested again by triangulation of sources. The results of this study indicate that the implementation of the assessment of early childhood learning outcomes in TK LKIA II Pontianak has not been done as a whole in accordance with the steps in the assessment of early childhood learning outcomes proposed by experts in their fields. The conclusion from this study is that the teacher has not yet carried out an assessment of early childhood learning outcomes in accordance with the existing steps. Keywords: Assessment, Learning Outcomes, Early Childhood